The effect of bone vibrator coupling method on the neonate auditory brainstem response. (3rd June 2019) - Stuart, Andrew; Nelson, Hannah M.
Abstract: Objective: The purpose of this study was to examine the effect of three bone vibrator coupling methods on the neonate auditory brainstem response (ABR). Design: A repeated measures design was employed. Three coupling techniques were utilised (i.e. hand-held, hand-held applied force gauge and elastic band). ABRs were evoked with a bone-conducted 30 dB nHL 4000 Hz CE-Chirp octave band stimulus. A temporal bone area supero-posterior auricular position for bone vibrator placement was utilised. Study Sample: Twenty-six healthy full-term neonates participated. Results: Replicated ABRs were recorded from all neonates for each coupling method. There was a statistically significant effect of coupling on wave V latency ( p  < 0.001) and amplitude ( p  < 0.001). There was no statistical difference between the elastic band and the hand-held force gauge coupling for wave V latency and amplitude ( p  > 0.05). However, the hand-held coupling method produced significantly longer wave V latency and smaller amplitude versus the elastic band and hand-held force gauge ( p  < 0.001). Conclusions: Bone vibrator coupling method affects the neonate ABR. Clinicians should be consistent with the choice of coupling while delivering controlled bone-conducted stimuli in ABR assessments in neonates and infants.